From the accounting graduate’s and the employer’s perspectives: Exploring the key roles in making skill acquisition and transfer happen - PAN, Gary (Institutional Knowledge at Singapore Management University, 2025)
While extant research has discussed how a teacher’s role may have to change when facilitating accounting students’ learning in today’s fast-moving accounting landscape, nevertheless, little is known about the roles played by the accounting graduate and the employer in a similar process. To plug this knowledge gap in the accounting education literature, this study aims to address the following research question: What are the key roles played by the accounting graduate and the employer in the process of skill acquisition and transfer from the university to the workplace? By applying Fitts and Posner’s (1967) three stages of learning and adopting a role perspective, we developed a process framework that depicts the roles played by the accounting graduate and the employer during the cognitive, associative and autonomous stages of skill acquisition and transfer. Our results suggest that the accounting graduate plays the roles of a self-directed learner, a resilient learner and an adept learner, whereas, the employer plays the roles of a supporter, a catalyst and a manager during the learning transfer process. Overall, our framework makes a unique contribution to the accounting education literature and offers relevant insights to enhancing graduate skill acquisition and transfer from the university to the workplace.